Первинний гіперпаратиреоз серед пацієнтів із хірургічною патологією щитоподібної залози - Шептуха, С. А.; Черенько, С. М. (Clinical Endocrinology and Endocrine Surgery, 2013)
Incidence and peculiarities of diagnostics of primary hyperparathyroidism (PHPT) among patients with surgical thyroid pathology using proper PHPT screening were analyzed in article. PHPT was revealed in 4.1 % of 5261 patients who were underwent thyroid surgery. All patients prepared to thyroid surgery should be mandatory inspected for the possible existence of parathyroid comorbidity. Determination of serum level of ionized calcium is the most suitable screening test followed by examination of parathyroid hormone, calcium in day's urine, phosphorus of blood, assessment of first line siblings with the purpose of exception of inherited forms of PHPT. Right establishing of PHPT allows a surgeon to chose the adequate extent of forthcoming intervention and avoid undesirable repeated operations in case of persistent hyperparathyroidism, connected with much higher risk of surgical complications.